2021
DOI: 10.1177/09697330211034250
|View full text |Cite
|
Sign up to set email alerts
|

The role of nurses' professional values during the COVID-19 crisis

Abstract: Background: The COVID-19 pandemic has produced high stress in nurses, affecting their professional quality of life. Different variables affect psychological stress response and professional quality of life. In this context, the role of professional values represents an interesting object of research. Objectives: To analyze the relationship between professional values, perceived stress, and professional quality of life among nurses during the COVID-19 crisis. Research design, participants, and research context:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
(49 reference statements)
1
14
0
1
Order By: Relevance
“…These events include technological advances ( Nes et al, 2021 ), changes in professional nursing practice ( Shun, 2021 ), and the diversity of patients and their belief systems (Ogbulo et al, 2018). The COVID-19 pandemic has affected how nurses perceive nursing care practice ( Chen et al, 2020 ) and their professional value system ( González-Pando et al, 2021 ), and competencies ( Li et al, 2021 ). In their study of nurses working with COVID-19-infected patients, Alloubani et al (2021) identified three themes about nurses' ethics and morality.…”
Section: Introductionmentioning
confidence: 99%
“…These events include technological advances ( Nes et al, 2021 ), changes in professional nursing practice ( Shun, 2021 ), and the diversity of patients and their belief systems (Ogbulo et al, 2018). The COVID-19 pandemic has affected how nurses perceive nursing care practice ( Chen et al, 2020 ) and their professional value system ( González-Pando et al, 2021 ), and competencies ( Li et al, 2021 ). In their study of nurses working with COVID-19-infected patients, Alloubani et al (2021) identified three themes about nurses' ethics and morality.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Despite the wealth of literature on moral distress, less is known about what the “moral” means in moral distress, that is, what beliefs and values undergird the nurse’s understanding of “the right thing to do.” A recent study identified ethics as the highest professional value for nurses. 5 At least two other articles have presented nurses’ perceptions of what characterizes a “good nurse” and how a nurse goes about doing the “right thing.” 6,7 These studies revealed personal virtues nurses considered important, but sources of the virtues were beyond the scope of these analyses.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified ethics as the highest professional value for nurses. 5 At least two other articles have presented nurses' perceptions of what characterizes a "good nurse" and how a nurse goes about doing the "right thing." 6,7 These studies revealed personal virtues nurses considered important, but sources of the virtues were beyond the scope of these analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The nurses shortage is a major global issue [1] . The situation has become even more critical with the outbreak of the Corona Virus Disease 2019 (COVID- 19), and the willingness of nurses to leave the profession has increased [2] . Clinical nurses have been faced with the uncertainty and risk of infection and a high workload, such as burdensome nursing tasks and caring for critically ill patients [3,4] , coupled with the physical discomfort and trauma from protection tools [5] , the perceived stress level of nurses is increasing and the individual's psychological defenses are constantly under attack [6] , making nurses vulnerable to low intentions to stay and physical or mental health problems, such as burnout, fatigue, acute stress disorder, anxiety, and depression [7][8][9][10][11] .…”
mentioning
confidence: 99%
“…The presence and development of perceived stress has become an important in uence on nurses' professional identity and an important predictor of an individual's physical and mental health [15][16][17] . Previous research on perceived stress in clinical nurses has focused on extrinsic factors such as signi cant workload, high-risk occupational environments, complex interpersonal relationships, ethical con icts, patient mortality outcomes, and closed workplaces [18][19][20][21][22][23] . Notably, previous studies have tended to emphasize how stress affects individuals, for example, the impact of stress on work-family con ict, innovative behavior, quality of life, etc.…”
mentioning
confidence: 99%